A comparative study of the solvent extraction of lanthanum(III) from different acid solutions. Issue 2 (3rd April 2021) - Agarwal, V.; Safarzadeh, M.S.; Galvin, J.
ABSTRACT: Solvent extraction of lanthanum(III) using the organic extractant 2-ethylhexyl phosphonic acid mono-2-ethylhexylester (PC88A) diluted in kerosene from three different aqueous media (sulfuric, nitric and chloride) was investigated. Eh -pH and speciation diagrams suggested that free lanthanum ion (La(III)) species predominate under the experimental conditions studied in this paper. The effects of several parameters on the extraction of lanthanum including initial pH (1.5–7), initial La(III) concentration (0.08–1.35 mmol/L), PC88A concentration (10–90 mmol/L) and temperature (25–55°C) were evaluated. In general, both hydrochloric and nitric acids were found to be more effective than sulfuric acid in terms of higher extraction of lanthanum. The stoichiometry of the extraction reaction and also the equilibrium constant were calculated. The extraction of La(III) was significantly enhanced by increasing pH and PC88A concentration and was only slightly increased by increasing temperature. Stripping studies showed that 1 mol/L acid concentration is adequate for effective stripping of lanthanum from the loaded organic. The stoichiometry of the extraction reaction was also investigated using density functional calculations and found to be in reasonable agreement with the experimental results.